Inversores fotovoltaicos multifuncionais aplicados na correção do fator de potência e na compensação de harmônicos - Paiva, Fabrício Nunes (2025)
The panorama of electricity systems around the world is undergoing a significant transfor mation, driven by the growing integration of alternative and renewable energy sources, such as solar, wind, and small hydroelectric plants (SHPs), among others. This phenomenon is widely known as distributed generation (DG). In Brazil, the photovoltaic sector stands out as a leader in plant installations, fueled by factors such as the widespread adoption of this technology, ease of installation, and the abundant solar radiation available in much of the country. However, integrating photovoltaic generation into electrical systems can pose challenges related to electric power quality, particularly with respect to the power factor. The generation of electricity by photovoltaic systems can lead to a decrease in the installation’s power factor, as the active power supplied to the load by the grid is reduced, while the reactive power remains unchanged compared to a system without photovoltaic generation. Another issue that can arise is the generation of harmonic cur rents caused by non-linear loads, which can compromise the integrity of equipment and conductors, as well as negatively affect the overall performance of the electrical system. In this context, the present paper proposes a methodology for improving power quality in a three-phase electrical system, utilizing a multifunctional converter based on a three-phase photovoltaic inverter with an LC filter (passive filter with inductor and capacitor). This system integrates both linear and non-linear loads and distributed solar generation. The approach aims to mitigate the negative impacts of low power factor and harmonic currents, optimizing the operation and reliability of the system. With the proposed multifunctional inverter, the power factor (lagging) was improved from 0.80 to 0.92, while harmonic current distortion was reduced from 15% to 3.34%. Additionally, another advantage observed in this work was the reduction in the number of proportional-resonant (PR) controllers in the control loop using dq0-coordinate control, with a single PR controller capable of controlling two harmonic frequency orders in the abc coordinates. The control strategy was validated through computer simulations implemented in the development environment of the MATLAB/Simulink® software